Inpatient hypoglycaemia in older people is associated with a doubling in the increased length of stay compared with the younger population. (17th October 2020) - Ruan, Yue; Moysova, Zuzana; Tan, Garry D; Lumb, Alistair; Davies, Jim; Rea, Rustam
Abstract: Background: Hypoglycaemia during hospital admission is associated with poor outcomes including increased length of stay. In this study, we compared the incidence of inpatient hypoglycaemia and length of stays among people of three age groups: ≤65 years, 65–80 years and >80 years old. Methods: The study was conducted using a 4-year electronic patient record dataset from Oxford University Hospitals NHS Foundation Trust. The dataset contains hospital admission data for people with diabetes. We analysed the blood glucose (BG) measurements and identified all level 1 (BG <4 mmol/l) and level 2 (BG <3 mmol/l) hypoglycaemic episodes. We compared the length of stays between different age groups and with different levels of hypoglycaemia. Results: We analysed data obtained from 17, 658 inpatients with diabetes who underwent 32, 758 hospital admissions. The length of stays for admissions with no hypoglycaemia were 3[1, 6], 3[1, 8] and 4[2, 11] (median[interquartile range]) days for age groups ≤65 years, 65–80 years and >80 years, respectively. These were statistically significantly lower ( P < 0.01 for all pairwise comparisons) than the length of stays for admissions with level 1 hypoglycaemia, which were 6[3, 13], 10[5, 20] and 12[6, 22] days, and level 2 hypoglycaemia, which were 7[3, 14], 11[5, 24] and 13[6, 24] days. Conclusions: In all age groups, admissions with either level 1 or level 2 hypoglycaemia were associated with an increased length of stay. However, in both the older groups, the length of stay increments were much higher (double) than the younger counterparts. The clinical consequences of hypoglycaemia were more severe in older people compared with the younger population.